Das manifestações discursivas multissemióticas ao multiletramento: procedimentos didático-pedagógicos - Moura, Rafael da Silva (2020)
This research has as a theme the approach of multimodal discursive genres in pedagogical practices, aiming at the promotion of multiliteracy. The objective is to elaborate and apply reading practices in the classroom, based on precepts from the French Discourse Analysis, as well as from Discursive Multimodality, in order to provide students with systematic moments of reading texts from discursive genres of multisemiotic nature With this objective, the following theoretical frameworks are mainly articulated: about discursive genres, Bakhtin (2009, 2011a, 2011b), Schneuwly and Dolz (2011); Kress (1996, 2000), Kress e van Leeuwen (2006), Lemke (1993, 2016), Rojo (2012, 2013) and Dionísio (2011, 2014), regarding discursive multimodality; Foucambert (1994), Petit (2008) and Silva (1981), about reading practices; New London Group (2000), Kalantzis and Cope (2000), Lemke (1993, 2016) and Rojo (2012, 2013), with regard to the multiliteracy; Maingueneau (2008) in relation to Global Semantics. In order to enable the production of reading practices, some of these theoretical categories are associated in the engendering of a methodological device that facilitates the analysis of enunciativediscursive aspects inscribed in multimodal texts. As for the methodology, it is an exploratory and bibliographical research, developed through action research, carried out in a 6th grade elementary school, from a private school, in the city of Sarandi (RS). As a motivating corpus, advertisements were used, which bring together multiple languages in their semantic constitution, carried in different media and with different discursive purposes. As a general result, it is noteworthy that pedagogical practices based on multimodal genres potentiate and boost language teaching, since they bring the learner closer to communicative-interactive situations proper to his discursive reality, thus assisting in the acquisition of the multiliteracy of this audience. In addition, this research fosters the development of didactic-pedagogical methodologies aimed at strengthening the teaching and learning process of reading skills.